2015
DOI: 10.1016/j.ymgme.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Arginine:glycine amidinotransferase (AGAT) deficiency: Clinical features and long term outcomes in 16 patients diagnosed worldwide

Abstract: AGAT deficiency is a treatable intellectual disability. Early diagnosis may prevent IDD and myopathy. Patients with unexplained IDD with and without myopathy should be assessed for AGAT deficiency by determination of urine/plasma GAA and cerebral creatine levels (via brain MRS), and by GATM gene sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…Further concerns have been raised about a possible GAA neurotoxicity in inborn errors of creatine metabolism, with neurocognitive dysfunction in GAMT deficiency accompanied by GAA accumulation and creatine deficit in the brain (Hanna-ElDaher et al 2015). A more severe phenotype reported in GAMT deficiency, as compared to AGAT deficiency which is characterized by low levels of both GAA and creatine (Stockler-Ipsiroglu et al 2015), suggests specific GAA-induced neuropathological features. The possibility that dietary GAA accumulates in the normal brain to toxic levels (~ 300-fold above normal in the brain of GAMT deficient patients) and contributes to neurotoxicity is highly unlikely due to transport limitations (Braissant 2012) yet no conclusive human studies are available so far.…”
Section: Page 5 Of 10mentioning
confidence: 95%
“…Further concerns have been raised about a possible GAA neurotoxicity in inborn errors of creatine metabolism, with neurocognitive dysfunction in GAMT deficiency accompanied by GAA accumulation and creatine deficit in the brain (Hanna-ElDaher et al 2015). A more severe phenotype reported in GAMT deficiency, as compared to AGAT deficiency which is characterized by low levels of both GAA and creatine (Stockler-Ipsiroglu et al 2015), suggests specific GAA-induced neuropathological features. The possibility that dietary GAA accumulates in the normal brain to toxic levels (~ 300-fold above normal in the brain of GAMT deficient patients) and contributes to neurotoxicity is highly unlikely due to transport limitations (Braissant 2012) yet no conclusive human studies are available so far.…”
Section: Page 5 Of 10mentioning
confidence: 95%
“…One of the primary concerns in designing treatment protocols should be targeting the critical periods in which Cr is necessary to facilitate cognitive processes. It has been shown that early‐life Cr supplementation provides a greater cognitive improvement than later life treatment in individuals with mutations of the Cr‐synthesis genes Arginine: glycine amidinotransferase ( AGAT ) or guanidinoacetate‐methyltransferase (GAMT) . Mitochondrial dysfunction or CK inhibition reduces the growth and dendritic arborization of cerebellar Purkinje cells in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…As above stated (see Section 1), the body obtains the creatine it needs partly from dietary sources and partly from endogenous synthesis and arginine:glycine amidinotransferase (AGAT) deficiency …”
Section: Creatine Administration In Conditions Where Creatine Is Missmentioning
confidence: 99%
“…Two rare diseases exist where the body cannot synthesize creatine due to genetic lack of the relevant enzymes: guanidinoacetate methyltransferase (GAMT) deficiency and arginine:glycine amidinotransferase (AGAT) deficiency …”
Section: Creatine Administration In Conditions Where Creatine Is Missmentioning
confidence: 99%